The Impact of Tahfidz and Qiro'ati on the Learning Outcomes of Junior High School Students in Islamic Education - Iwan Kurniawan. ZP; Muhammad Zakir Husain (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
ENGLISH: The Impact of Tahfidz and Qiro'ati on the Learning Outcomes of Junior High School Students in Islamic EducationObjective: This study aims to examine the effect of the Foundation Program, which includes the Tahfidz (Qur'an memorization) program and the Qiro'ati (Qur'anic recitation) method, on students' learning outcomes in Islamic education at Al SMP Islam Al-Hasanah, Kota Bengkulu. Method: This research employs a quantitative approach. Data were collected through observation, questionnaires, and documentation. The data analysis technique used in this study is simple linear regression analysis. Results: The findings indicate no significant influence of the Tahfidz program and the Qiro'ati method on students' learning outcomes in Islamic education. The contribution of the Foundation Program variable (X) to improving Islamic education learning outcomes (Y) is only 0.1%, as shown by the coefficient of determination. Conclusion: The Tahfidz program and the Qiro'ati method do not significantly improve Islamic education learning outcomes at SMP Islam Al-Hasanah, Kota Bengkulu. Contribution: This research provides valuable insights for teachers regarding the importance of optimizing Tahfidz- and Qiro'ati-based teaching methods to enhance the effectiveness of teaching and learning processes in Islamic education.INDONESIAN: Pengaruh Tahfidz dan Qiro’ati terhadap Hasil Belajar Siswa SMP pada Mata Pelajaran Pendidikan IslamTujuan: Penelitian ini bertujuan untuk mengetahui pengaruh program yayasan terhadap hasil belajar Pendidikan Agama Islam pada siswa di SMP Islam Al-Hasanah, Kota Bengkulu: Jenis penelitian menggunakan metode kuantitatif. Teknik pengumpulan data penelitian melalui observasi, angket, dan dokumentasi. Teknik analisis data dalam penelitian ini dengan menggunakan analisis regresi linear sederhana. Hasil: Tidak terdapat pengaruh yang signifikan antara program Tahfidz dan metode Qiro’ati terhadap peningkatan hasil belajar Pendidikan Agama Islam. Kontribusi yang diberikan oleh variabel program yayasan (X) terhadap variabel peningkatan hasil belajar Pendidikan Agama Islam (Y) hanya sebesar 0.1% yang ditandai dengan nilai koefisien determinan sebesar 0.1%. Kesimpulan: Tidak terdapat pengaruh yang signifikan antara program Tahfidz dan metode Qiro’ati terhadap peningkatan hasil belajar Pendidikan Agama Islam SMP Islam Al-Hasanah, Kota Bengkulu. Kontribusi: Penelitian ini berkontribusi sebagai wawasan kepada guru tentang pentingnya metode pengajaran berbasis tahfidz dan qiro'ati sehingga dapat diterapkan secara optimal dalam kegiatan belajar mengajar.